The CIITA genetic polymorphism rs4774*C in combination with the HLA-DRB1*15:01 allele as a putative susceptibility factor to multiple sclerosis in Brazilian females - Eduardo R. Paradela; Soniza V. Alves-Leon; André L. S. Figueiredo; Valéria C. S. R. Pereira; Fabíola Malfetano; Letícia F. Mansur; Simone Scherpenhuijzen; Luciana A. Agostinho; Catielly F. Rocha; Fernanda Rueda-Lopes; Emerson Gasparetto; Carmen L. A. Paiva (Arquivos de Neuro-Psiquiatria)
The objective of this study was to investigate the association between the HLA alleles at the DQA1, DQB1 and DRB1 loci, the CIITA genetic polymorphisms -168A/G and +1614G/C, and susceptibility to multiple sclerosis (MS) in a sample from Rio de Janeiro State, Brazil. Furthermore, we wished to determine whether any of these associations might be more significant in women compared with men. DNA samples from 52 relapsing-remitting MS (RRMS) patients and 126 healthy controls matched for sex and age were analyzed. We identified a significant HLA-DRB1*15:01-MS association that was female-specific (Odds Ratio (OR) = 4.78; p = 0.001). Furthermore, we observed that the +1614G/C mutation in combination with the HLA-DRB1*15:01 allele increased susceptibility to MS in females (OR = 4.55; p = 0.01). Together, these findings highlight the polygenic nature of MS.